2000
DOI: 10.1111/j.1747-5457.2000.tb00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression and Retardation of Vitrinite Reflectance, Part 2. Derivation and Testing of a Kinetic Model for Suppression

Abstract: The presence of suppressed and retarded vitrinite reflectance (VR) data introduces a number of dificulties into the prediction of hydrocarbon generation in sedimentary basins. Although the effects of suppression can be removed from measured VR values manually, a kinetic model for suppressed vitrinite maturation would enable both suppressed and unsuppressed VR values to be predicted using thermal histories derived from basin modelling. The evaluation of hydrocarbon generation fiom suppressed and unsuppressed vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The 5620 m sample from the overpressured system displays R o value of 0.77%, which seems to be abnormally low. Abnormally low R o values in overpressured systems have been observed in many basins such as the Yinggehai Basin [28,34] , the North Sea Basin [32,33,36,37] , and the Utah Basin [46] . These abnormally low R o values in overpressured rocks are attributed to overpressure retardation of organic matter maturation.…”
Section: Mechanisms Of Overpressure Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5620 m sample from the overpressured system displays R o value of 0.77%, which seems to be abnormally low. Abnormally low R o values in overpressured systems have been observed in many basins such as the Yinggehai Basin [28,34] , the North Sea Basin [32,33,36,37] , and the Utah Basin [46] . These abnormally low R o values in overpressured rocks are attributed to overpressure retardation of organic matter maturation.…”
Section: Mechanisms Of Overpressure Generationmentioning
confidence: 99%
“…Overpressure or overpressure-related processes may retard organic matter maturation, and therefore influence the hydrocarbon generation histories of overpressured source rocks [28,[32][33][34][35][36][37] .…”
Section: Mechanisms Of Overpressure Generationmentioning
confidence: 99%
“…A hydrocarbon generation model based on the Arrhenius equation has been established for normal-pressure environments, implying that pressurerelated effects have little influence on organic matter maturation and hydrocarbon generation. However, a growing body of research shows that in a highpressure system, different maturation reactions may occur because of differences in volume expansion, causing differential retardation of the physical and chemical reactions between the products generated and the organic matter (Cecil et al, 1977;Price and Wenger, 1992;Domine and Enguehard, 1992;McTavish, 1998;Carr, 1999;2000a;2000b;2003;Hao et al, 1995;1998;Wang et al, 2006;2007a, 2007bLe Bayon et al, 2011).…”
Section: Effects Of Pressure On Om Maturationmentioning
confidence: 99%
“…Furthermore, many maturity models which explorationists have developed are either Lopatin's Time-Temperature Indexes (TTIs) produced by calibrating the maturity with time and temperature in basins (Waples, 1980;Goff, 1983), or kinetically based (Ritter, 1984;Sweeney and Burnham, 1990;Li et al, 2008). Recently, more laboratory studies focus on the effects of pressure on VR (Price and Wenger, 1992;Hao et al, 1995) which have shown that pressure or overpressure can be incorporated into a kinetic model (Dalla Torre et al, 1997;Carr, 1999Carr, , 2000Zou and Peng, 2001), and on any other parameters capable of influencing the maturity, e.g. heating rate, lithology, hydrogen index and dry or wet conditions in laboratory pyrolysis (Khorasani and Michelsen, 1994;Huang, 1996;Lewan, 1998).…”
Section: Introductionmentioning
confidence: 98%